Quantitative assessment of temporal skin elasticity using shear wave elastography in pediatric cochlear implant users. (October 2020) - Yildiz, Muhammet; Ozkan, Mehmet Burak; Selcuk, Omer Tarik; Cetinkaya, Erdem Atalay; Ensari, Nuray; Yilmaz, Nevreste Didem Sonbay; Gur, Ozer Erdem
Abstract: Objective: To evaluate temporal skin thicknesses and stiffness values using shear wave elastography (SWE) in asymptomatic pediatric patients who underwent cochlear implantation. Subjects and methods: Sixty-four deafened pediatric patients with unilateral cochlear implant (CI) who had no complications were enrolled. The age, sex, weight, height, body mass index (BMI), CI side, duration of CI use and CI device brand of all participants were noted. Temporal skin thickness and stiffness values were measured from implanted and contralateral unimplanted sides using SWE. Results: The mean skin thickness measurements of implanted and unimplanted sides were 11.87 ± 3.42 and 5.34 ± 1.56 mm, respectively. The mean skin stiffness measurements of implanted and unimplanted sides were 3.08 ± 0.7 and 1.29 ± 0.26 m/s, respectively. There were statistically significant differences in skin thickness and stiffness between implanted and unimplanted sides (P < .001, P < .001). The mean skin thickness and stiffness measurements did not differ among types of CI devices (P = .948, P = .362). Age had positive correlation with implanted (P < .001, P = .019) and unimplanted sides (P < .001, P < .001) skin thickness and stiffness. BMI had positive correlation with implanted (P < .001, P = .023) and unimplanted sides (P < .001, P < .001) skin thickness and stiffness. Duration of CI use had positive correlation with implanted side skin thickness (P < .001) and stiffness (P = .031). Conclusion: Temporal skin thickness and stiffness increase after CI surgery. SWE has the potential to improve diagnostic accuracy, and our results may provide important data for evaluation of clinical entities that affect temporal skin structures.